(x-3/5)-1= (x-5)/4
Hello joshua17hernandez!
You use brackets, I hope you know, what they mean. So you want to solve
$\displaystyle (x - \frac{3}{5}) - 1 = \frac{x-5}{4}$, right? Then
$\displaystyle x - \frac{3}{5} - \frac{5}{5} = \frac{x}{4} - \frac{5}{4}$
$\displaystyle x - \frac{8}{5} = \frac{x}{4} - \frac{5}{4}$
$\displaystyle - \frac{8}{5} + \frac{5}{4} = \frac{x}{4}-x$
$\displaystyle - \frac{32}{20} + \frac{25}{20} = \frac{x}{4}-\frac{4x}{4}$
$\displaystyle -\frac{7}{20} = \frac{-3x}{4}$
$\displaystyle -\frac{7*4}{20} = -3x$
$\displaystyle -\frac{7}{5} = -3x$
$\displaystyle -(-\frac{7}{5*3}) = x$
$\displaystyle +\frac{7}{15} = x$
Do you understand?
Rapha
Oh yes, I did use the bracket...but i used them the wrong way sorry i meant to write it like this...
x-3 -1= x-5
5 4
wait the 4 is suppose to be under the x-5
this is my real problem i kept getting x=9
but my book says the answer is x=-7 and i don't seem to understand how they got that answer.
Can you help once again?
you mean (x-3)/5 - 1 = (x-5)/4? ok
multiply both sides WITH 20, the product of 5 and 4.
20(x-3)/5 - 20 (1) = 20(x-5)/4, cancel common factors
4(x-3) - 20 = 5(x-5);
4x - 12 - 20 = 5x - 25
4x - 5x = -25 + 32
-x = 7
x = -7.
Maybe this IS THE ANSWER that you want